Improving the Microstructure and Electrical Properties of Aluminum Induced Polysilicon Thin Films Using Silicon Nitride Capping Layer. (25th June 2014) - Weng, Min-Hang; Pan, Cheng-Tang; Huang, Chien-Wei; Yang, Ru-Yuan
Abstract : We investigated the capping layer effect of SiN x (silicon nitride) on the microstructure, electrical, and optical properties of poly-Si (polycrystalline silicon) prepared by aluminum induced crystallization (AIC). The primary multilayer structure comprised Al (30 nm)/SiN x (20 nm)/a-Si (amorphous silicon) layer (100 nm)/ITO coated glass and was then annealed in a low annealing temperature of 350°C with different annealing times, 15, 30, 45, and 60 min. The crystallization properties were analyzed and verified by X-ray diffraction (XRD) and Raman spectra. The grain growth was analyzed via optical microscope (OM) and scanning electron microscopy (SEM). The improved electrical properties such as Hall mobility, resistivity, and dark conductivity were investigated by using Hall and current-voltage (I -V ) measurements. The results show that the amorphous silicon film has been effectively induced even at a low temperature of 350°C and a short annealing time of 15 min and indicate that the SiN x capping layer can improve the grain growth and reduce the metal content in the induced poly-Si film. It is found that the large grain size is over 20  μ m and the carrier mobility values are over 80 cm 2 /V-s.